POTENSI SELEDRI (Apium graveolens L) DAN STROBERI (Fragaria sp) SEBAGAI MINUMAN FUNGSIONAL APIGA TERHADAP TEKANAN DARAH - NUGRAHASARI, CATURINI MEIDYA; Sutjiati, Endang; Mustofa, Annasari (Jurnal Pendidikan Kesehatan (e-Journal), 2023)
Hypertension is a non-communicable disease that is a health problem in the world, based on Riskesdas data, the prevalence of hypertension sufferers in the population aged 18 years in Indonesia has increased from 25.8% in 2013 to 34.1% in 2018. (Ministry of Health, 2019). Celery has a weakness in taste, it is necessary to add other food ingredients, namely strawberries and give the name APIGA Drink from the Latin name, celery (Apium graveolens L) and strawberry (Fragaria sp). The purpose of this study was to determine the potential of celery (Apium graveolens L) and strawberries (Fragaria sp) as APIGA functional drinks (Apium and Fragaria) on systolic and diastolic blood pressure in outpatient hypertension patients at Yosomulyo Public Health Center Banyuwangi. This type of research is pre-experimental, with a one-group pretest-pottest design, with 30 patients as respondents. Giving drink once a day for 3 consecutive days as much as 250 ml/g. Normality test using Shapiro Wilk. Statistical analysis used the Wilcoxon signed test and paired t-test. The average systolic blood pressure before being given the APIGA functional drink intervention was 162.23 mmHg in the stage II hypertension category and the average diastolic blood pressure was 94.67 mmHg included in the stage I hypertension category. The average systolic blood pressure after being given the APIGA functional drink intervention was 145.57 mmHg in the category I hypertension and the average diastolic blood pressure was 84.20 mmHg included in the prehypertension category. It can be concluded that there is a significant effect between systolic and diastolic blood pressure in patients with hypertension after being given the APIGA functional drink intervention on the blood pressure of outpatients with hypertension at Yosomulyo Public Health Center Banyuwangi with p value = 0.000. Kata Kunci : Seledri, Stroberi, Tekanan darah, Hipertensi